Alle dingen nieuw: Theologie uit genade - Borgman, Erik (Tijdschrift voor theologie, 2012)
Starting from the observation that in its current self-understanding, theology is unable to really think through the situation in which we find ourselves, this article attempts to find a way forward. Its motto is derived from Leonard Cohen’s song ‘Anthem’: ‘There is a crack in everything, that is how the light gets in’. We as human beings are not self-sufficient or whole, our individual and collective histories do not neatly translate into successful projects, and the Christian tradition is not a comprehensive unity. From a Christian point of view, however, it is by brokenness that we are saved. In a first part it is argued that theology is not an analysis of faith. Rather, what is given in an existential manner in faith, has to be thought in theology. Faith is here first of all understood as the ability to experience crisis as grace. Following Thomas Aquinas, it is argued that this is what the Christian revelation implies: everything is an expression of God’s grace as is shown in the limitless love expressed in the life and death of Jesus Christ. Our shared sorrow, our desperate desire, our hope against hope are reflections of that love as the binding and sustaining force of creation, and thus manifestations of Christ’s enduring presence. A second part shows in what sense surrender to this love might be considered reasonable. By ourselves we cannot conclude that everything originates in, is sustained by and is directed towards self-giving love. However, once this is preached to us we recognize it as ‘fitting’ to what we experience ourselves and our world to be. There is a strong tension between our modern self-understanding and the discovery that we are ultimately sustained not by our own capacities, but by graceful love. This tension calls for conversion. In a Christian understanding, religion cannot be seen as the conviction of believers. Rather, it is a manner of existing and thinking that consciously depends on grace. Consequently, theology in this article is presented as intellectual contemplation. In Aquinas’ view, in contemplation we turn our consciousness into God’s temple by learning to see and experience everything in the light of God’s love. In the third and last part of this article, it is explained that grace leads to an attitude of poverty and vulnerability in the intellectual life. Aquinas’ principle that ‘grace does not destroy nature but perfects it’ has to be read as an exhortation to see everything from the restored viewpoint of grace. We are promised that all things will be made new (Revelation 21,5), and seeing them in this light means rediscovering their true and original sense.